Pengaruh Persepsi Label Halal dan Citra Merek Terhadap Keputusan Pembelian Pada Gerai Mixue Kondangjaya Karawang - Rohman, Syaiful; Fadilla, Arif (Peneliti.net, 2024)
This research aims to analyze the influence of halal label perceptions and brand image on purchasing decisions at the Mixue Kondangjaya Karawang outlet. This research uses a descriptive verification approach with quantitative methods. The population in the research were consumers who had previously purchased Mixue products at the Mixue Kondangjaya Karawang outlet, sampling using the Nonprobability Sampling method with incidental sampling technique with a total sample of 391 respondents. The test stages used are validity test, reliability test, classical assumption test, multiple linear regression analysis technique and hypothesis testing using t test, f test and coefficient of determination using SPSS 25 tools. The results of this research obtained perceptions of halal labels and brand image partially influence purchasing decisions at the Mixue Kondangjaya Karawang outlet with respective variable values of 24.5% and 40.6%. Meanwhile, the perception of the halal label and brand image simultaneously on purchasing decisions at the Mixue Kondangjaya Karawang outlet together had an influence of 55.7% on purchasing decisions.